A Systematic Review of Applying International Classification of Functioning, Disability, and Health in Child Speech and Language Impairment - Tahmineh Maleki; Yalda Kazemi (Vesnu Publications, 2016)
Introduction: There is a lack of knowledge on the International Classification of Functioning, Disability, and Health (ICF) framework in Iran. Thus, the aim of the present study was to familiarize speech and language pathologists with this framework and the quality of previous studies in this respect through a purposive review of published studies on the application of the ICF framework regarding speech and language impairments in preschool children. Materials and Methods: The keywords used included ICF and communication disorder, ICF and language impairment, and ICF and speech impairment. The main data banks searched included PubMed and Web of Knowledge and the search limit consisted of studies published between the years 2005 and 2015. Results: Based on inclusion/exclusion criteria, 6 of the 96 published documents were eligible to be reviewed. All studied papers asserted that the ICF framework, through providing a comprehensive view, provides a concept of children's speech and language impairment which can create a coherent interaction between empirical evidence and clinical observations. Therefore, it evaluates all obstacles and facilitators of communication for the child. This will result in a more effective and targeted assessment and treatment of speech and language impairments in children. Of all the themes present in the ICF framework, 735 themes were used in the reviewed articles, most of which were related to the activities and participation domains. Conclusion: Due to its components and their interaction, the ICF framework prevents the sole focusing of physicians, in a traditional and medical sense, on the structure and function of body organs. It provides a comprehensive view on the performance, function, and coordination of individual and environmental factors for the child. The review of these texts shows that they also emphasize the application of this comprehensive approach in the accurate assessment and treatment of speech and language impairments. The quality analysis of the studies showed that the majority of the studies regarding this topic were published in a non-experimental and non-research format. Moreover, very few experimental studies have been performed in this regard, which did not surpass descriptive studies in terms of quality.